Peran Ekonomi Kreatif Subsektor Kuliner dan Kriya dalam Menciptakan Kesempatan Kerja di Kabupaten Kutai Kartanegara - Iskandar, Iskandar; Roy, Juliansyah; Lestari, Diana (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the role of the culinary and craft subsectors in generating employment opportunities in Kutai Kartanegara Regency during the period 2021–2024. The research is grounded in the region’s economic transformation from extractive industries toward a creative economy driven by local culture and innovation. A descriptive qualitative approach was applied, utilizing data collection methods such as documentation, in-depth interviews, and direct observation of creative economy actors. The findings reveal that the culinary subsector dominates the local creative economy, comprising 3.101 active entrepreneurs, while the kriya subsector includes 287 actors. However, only 336 culinary businesses hold halal certification, which serves as a crucial indicator of sustainability and market access. Both subsectors have made significant contributions to job creation, particularly through home-based and community-driven enterprises, and have empowered marginalized groups such as women and youth. Key enabling factors include the abundance of local raw materials, rich cultural heritage, government support programs, and access to digital platforms. Conversely, barriers include low digital literacy, limited access to capital, lack of product innovation, and insufficient long-term business mentoring. This research concludes that the culinary and kriya subsectors play a vital role in expanding employment and supporting an inclusive and sustainable regional economy.